The Islamic Financial System as a Solution to Poverty Problems in Indonesia - Wahidatun Nafiah Alfarda; Saifudin Yusuf; Hardining Estu M; Imam Nur Ngaini; Andrean Permadi (El-Qish: Journal of Islamic Economics, 2024)
Poverty is one of the main challenges faced by Indonesia, a country rich in natural resources and human potential. The presence of Islamic financial system is considered suitable for poverty alleviation programs. Islamic economics adheres to the principle of synergy (ta'awun) by creating economic justice to equalize the distribution of income and wealth, which is the goal of Islamic financial system. This research is a qualitative study with an inductive reasoning approach through a library research process. The data sources used to build the concept are secondary data derived from previous research in the form of articles discussing poverty. The research results show that the poverty rate in Indonesia tends to decrease from year to year. Market and banksbased industry have philosophical principles and operational bases that are integrated with social values and economic activities. Poverty will be reduced if all elements of society work together to support programs originating from the government and from other institutions, such as banking support for poverty alleviation.